Pengembangan Media Pembelajaran Berbasis Kuis Interaktif Baamboozle pada Mata Pelajaran IPAS Kelas V SD Negeri 060872 Medan - Rahma Sari Dewi; Lidia Simanihuruk; Nurhairani Nurhairan; Fahrur Rozi; Winara Winara (Universitas Batanghari Jambi, 2026)
The purpose of this study is to determine the validity of learning media, to determine the practicality of learning media and the effectiveness of learning media developed on human respiratory system materials. The type of research is research and development (R&D) using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The results of validation by material experts on Baamboozle's interactive quiz-based learning media obtained a score of 92% with the criterion of